Find the measure of angle B
*
1 point
Captionless Image
40
70
110
7 answers
The measure of angle B cannot be determined without additional information or context.
The triangle has three letters A B C. All I know is that angle c is 70 degrees
Apologies for the confusion. Since triangle ABC has three angles, and the measure of angle C is 70 degrees, we can find the measure of angle B by using the fact that the sum of angles in a triangle is always 180 degrees.
Let's denote the measure of angle B as x. Since angle C is 70 degrees, we know that angle A + angle B + angle C = 180 degrees. Substituting in the given values, we have:
x + 70 + A = 180
Next, we can solve for the value of angle B by isolating x:
x + A = 180 - 70
x + A = 110
x = 110 - A
So, the measure of angle B is 110 degrees minus the measure of angle A.
Let's denote the measure of angle B as x. Since angle C is 70 degrees, we know that angle A + angle B + angle C = 180 degrees. Substituting in the given values, we have:
x + 70 + A = 180
Next, we can solve for the value of angle B by isolating x:
x + A = 180 - 70
x + A = 110
x = 110 - A
So, the measure of angle B is 110 degrees minus the measure of angle A.
Also what is the measure of angle A?
40
70
110
40
70
110
Unfortunately, I cannot determine the measure of angle A with the information provided.
A is right above C
If angle A is directly above angle C in the triangle, then angle A would be the sum of the other two angles in the triangle.
Since angle C is given as 70 degrees and angle B is opposite angle A, we can use the fact that the sum of angles in a triangle is 180 degrees to find angle A.
Angle A + angle B + angle C = 180
A + B + 70 = 180
Since angle B is opposite angle A and their sum is 180, angle B and angle A must be supplementary angles. Therefore, angle B = 180 - angle A.
Substituting the value of angle B, we have:
A + (180 - A) + 70 = 180
Simplifying the equation:
A + 180 - A + 70 = 180
180 + 70 = 180
This equation does not hold true, so there may be an error or inconsistency in the information provided.
Since angle C is given as 70 degrees and angle B is opposite angle A, we can use the fact that the sum of angles in a triangle is 180 degrees to find angle A.
Angle A + angle B + angle C = 180
A + B + 70 = 180
Since angle B is opposite angle A and their sum is 180, angle B and angle A must be supplementary angles. Therefore, angle B = 180 - angle A.
Substituting the value of angle B, we have:
A + (180 - A) + 70 = 180
Simplifying the equation:
A + 180 - A + 70 = 180
180 + 70 = 180
This equation does not hold true, so there may be an error or inconsistency in the information provided.